2012
DOI: 10.1007/s10841-012-9509-9
|View full text |Cite
|
Sign up to set email alerts
|

Is there a benefit of excluding sheep from pastures at flowering peak on flower-visiting insect diversity?

Abstract: Permanent grasslands are an important habitat for insect communities, including pollinator populations which are in pan-European decline. Here, we investigated the benefits of temporarily excluding sheep from pastures on butterfly (Lepidoptera: Rhopalocera and Zygaenidae) and bumblebee (Hymenoptera: Bombidae) communities in two semi-natural grasslands differing in soil fertility and surrounding landscapes. We compared the impact of continuous grazing against rotational grazing (RG) at the same stocking rate bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Numbers to the right are species-wise information on number of occurrences and total number of sites in the models. Dewenter and Tscharntke, 1997;Franzén and Nilsson, 2008;Wallis de Vries et al, 2012;Scohier et al, 2013). However, Sjödin et al (2008) found that butterflies only responded to vegetation height and not to flower abundance.…”
Section: Richness Is Positively Affected By Abundance Of Flowers Withmentioning
confidence: 98%
“…Numbers to the right are species-wise information on number of occurrences and total number of sites in the models. Dewenter and Tscharntke, 1997;Franzén and Nilsson, 2008;Wallis de Vries et al, 2012;Scohier et al, 2013). However, Sjödin et al (2008) found that butterflies only responded to vegetation height and not to flower abundance.…”
Section: Richness Is Positively Affected By Abundance Of Flowers Withmentioning
confidence: 98%
“…For instance, the analysis of underlying mechanisms involved in grazing management (i.e. relationships between stocking rate and sward heterogeneity, animal selectivity) can explain the success or failure of grazing practices aiming to combine production and biodiversity conservation (Scohier et al, 2013). In addition, the ecological rationale of traditional small-scale systems needs to be analyzed to understand the mechanisms contributing to their success.…”
Section: Scaling-up Agroecological Apsmentioning
confidence: 99%
“…Body size class is a three-level factor (small, medium, large), but the level "small" has been excluded from the analysis, since it was represented by only one pollinator species (see Appendix B1 for details on the assignment of insect traits). Significant (p < .05) results are printed in bold and their differences are visualized in Figure 6 Explanatory factors reducing the diversity of pollinator groups (Scohier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%